PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 5 KOTABARU TAHUN PELAJARAN 2017/2018 - Faisal Batennie Batennie; Rudy Suryana (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
ABSTRACTÂ The purpose of this research is (1) To know the application of Make A Match Learning Model to student learning outcomes in Arithmetic Social. (2) To know the difference of student learning result by using Make A Match learning model and students using conventional model in SMP Negeri 5 Kotabaru.The method which used in this research is quantitative descriptive research, which is a lot of research required to use numbers, ranging from data collection, interpretation there is data, and appearance of the results. In addition data in the form of numbers, in quantitative research there is also data in the form of qualitative information.The results showed that the average value obtained from the results of student learning evaluation with the application of the model of cooperative learning type Make A Match can be applied in SMP Negeri 5 Kotabaru seen from the average value of the evaluation results of learning 75.42 with good qualifications. The results also show that there is no difference in learning outcomes using conventional learning modeland using the Make A Match learning model. This can be seen from tcount<ttable(-0.116 <1.679) which means that if -ttable then H0 is accepted.Keywords: Cooperative Learning Model Type Make A Match